Impedance characteristics of aluminum with sol-gel ceria protective coating during the exposure to chloride corrosion agent - Vladimir V. Panić; Stanković Vesna B. Mišković (Zaštita Materijala)
Electrochemical impedance characteristics of bare Al and Al with CeO2 coating prepared sol-gel procedure from the ceria sol are investigated. The corrosion behavior is monitored during the exposure to 3 wt. % NaCl aqueous solution. Experimental data are fitted to various equivalent electrical circuits with special attention to inductive features. Equivalent electrical circuits involving inductivity represent impedance response equally well as the ones without inductivity, although the parameter values gained from the former correspond better to the proposed model of physicochemical changes during corrosion of investigated samples.